Implications of LDH in patients with coronavirus disease 2019 pneumonia - Mu, Tong; Wang, Xingguang; Lu, Zhiming; Tong, Jia (Frontiers in Cellular and Infection Microbiology, 2023)
Abstract：To explore the value of serum lactic dehydrogenase(LDH)in the early diagnosis and prognostic evaluation of pneumonia associated with novel coronavirus infection. A total of 101 patients with COVID-19 pneumonia were included in the study. According to the severity of initial chest computed tomography ( CT ) , the patients were divided into ordinary pneumonia group and severe pneumonia group, and divided into remission group and non-remission group according to the changes of chest CT after medication treatment. The differences in general characteristics, underlying diseases,clinical symptoms,laboratory findings and imaging examination outcomes between groups were observed retrospectively. To analyze the diagnostic performance of LDH, receiver operating characteristic (ROC) curves were constructed, the area under the curve (AUC) was calculated. Compared with ordinary pneumonia patients, patients in severe group presented with significantly higher LDH, neutrophil count, HS-TnT, C-reactive protein (CRP) , human serum amyloid A (SAA) , N-terminal pro-brain natriuretic peptide (NT-proBNP), and D-dimer.Compared with remission patients, non-remission patients presented with significantly higher LDH, neutrophil count, HS-TnT, CRP, SAA, procalcitonin (PCT), creatine kinase-MB mass (CKMB_M), NT-proBNP and D-dimer. In multivariate logistic regression analysis,we found that LDH (odds ratio [OR], 1.015; 95% confidence interval [CI], 1.006-1024; P = 0.001) and neutrophil count (odds ratio[OR], 1.352; 95% CI , 1.008-1.811; P = 0.044) were independently associated with exacerbation in COVID-19 patients. For ROC analysis, the AUC was 0.833 (95% CI, 0.729-0.936; p < 0.001) when we use the LDH value of 256.69 U/L to discriminate the ordinary pneumonia and severe pneumonia patients. The AUC was 0.759 (95% confidence interval, 0.603-0.914; p = 0.008) and the sensitivity is 92.3% when we combined the LDH (cutoff value 258.46 U/L) and the neutrophil count (cutoff value 6.76×10 9 /L) to discriminate remission and non-remission patients. The level of LDH is associated with the severity of COVID-19 pneumonia, and can be used as important indicators to evaluate the prognosis of patients.